Réponses

2014-05-17T17:20:22+02:00
H(a)=(-2a+1)/(a-1)
h(b)=(-2b+1)/(b-1)
h(a)-h(b)=(((-2a+1)(b-1))/((a-1)(b-1)))-(((-2b+1)(a-1))/((a-1)(b-1)))
=(-2ab+2a+b-1+2ab-2b-a+1)/((a-1)(b-1))
=(a-b)/((a-1)(b-1))
comment tu a fais a avant derniere pour obtenir a-b tu a fais quoi a -2ab+2a.........................
2014-05-17T17:24:12+02:00
H(a)= \frac{(-2a+1)}{(a-1)}

h(b)= \frac{(-2b+1)}{(b-1)}

h(a)-h(b)=(( \frac{(-2a+1)(b-1))}{((a-1)(b-1)} ))-(( \frac{(-2b+1)(a-1)}{(a-1)(b-1)} ))
=(-2ab+2a+b-1+2ab-2b-a+1)/((a-1)(b-1))
=(a-b)/((a-1)(b-1))